Report of Adverse Events Associated With Cutaneous Procedures: Update From the CAPER Registry - Sabrina S. Smith; Michael D. Yi; Elizabeth Zhang; Joycie Chang; Thanvi Gullapalli; Doroteja Dragovic; Vanessa J. Lazaro‐Camp; Ashish C. Bhatia; Arisa Ortiz; Murad Alam (Lasers in Surgery and Medicine, 2026)
ABSTRACT Objectives To systematically evaluate submissions to the CAPER database by analyzing procedural context, characteristics of reported adverse events (AEs), and provider involvement in order to identify patterns with potential implications for patient safety. Methods A retrospective review of all reports submitted to the CAPER database from March 2021 to August 2025 was conducted, categorizing cases by procedure type, reported AE, and provider involved. Results In total, 199 reports describing 298 AEs across 35 various cutaneous procedures were submitted to the CAPER registry from March 2021 to August 2025. Dermatologists performed 62% of reported procedures, while non‐dermatologist physicians, non‐physicians, and unknown providers accounted for 38%. Filler injections, ablative laser resurfacing, and non‐ablative laser treatments were the most frequently reported procedures. Although dermatologists performed most procedures represented in the registry, 51% of reported AEs were associated with procedures performed by non‐dermatology providers. Erythema and scarring were among the most frequently reported AEs, while rare but serious events, including vascular compromise and necrosis, were reported following injectable and energy‐based procedures performed by a variety of provider types, including non‐physicians. Conclusions The CAPER registry provides valuable insight into AEs associated with cutaneous procedures and may help identify emerging safety concerns related to new devices or techniques. Broader engagement with AE reporting systems may inform best practices and improve patient safety, particularly as cutaneous procedures increasingly occur outside traditional clinical settings.